1943
DOI: 10.1113/jphysiol.1943.sp004019
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the vasomotor reflexes produced by stimulating mammalian sensory nerves

Abstract: It has often been suggested that afferent impulses, in response to a nocuous stimulus, have a part in initiating the changes in blood pressure which may follow severe injury. The idea gets an added interest from some recent suggestions that these impulses are carried in at least two types of fibre, the delta fibre and the unmyelinated C fibre [Zotterman, 1939] Hughes & Gasser [1935] found that there is still a vasomotor reflex if all the fibres in the sensory nerve except the unmyelinated C fibres have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1944
1944
1996
1996

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…This demon strated that the response was refl ex in nature with the afferent limb located in the dorsal root. Other experiments have demonstrated that electrical activation of afferent fibers from muscle can elicit cardiac responses similar to those that accompany exercise, and these studies also suggest that the fibers involved are probably unmyelinated or small myelinated ones (48)(49)(50)(51). The changes even include an increase in left ventricular contractile state (50).…”
Section: Cardiovascular Control Mechanisms During Static Exercisementioning
confidence: 93%
“…This demon strated that the response was refl ex in nature with the afferent limb located in the dorsal root. Other experiments have demonstrated that electrical activation of afferent fibers from muscle can elicit cardiac responses similar to those that accompany exercise, and these studies also suggest that the fibers involved are probably unmyelinated or small myelinated ones (48)(49)(50)(51). The changes even include an increase in left ventricular contractile state (50).…”
Section: Cardiovascular Control Mechanisms During Static Exercisementioning
confidence: 93%
“…The enhancement of excitatory spinal sympathetic reflexes by strychnine (Langley, 1924) may also have an origin in such a mixed input, because strychnine is reported to depress specifically inhibitory processes (Bradley, Easton & Eccles, 1953;Kuno, 1957). Furthermore, mixed effects from given nerves might explain the type of response in more intact preparations where one frequency of stimulation resulted in an increase of blood pressure and a different stimulation frequency a decrease (Gordon, 1943). Finally, it is possible that inhibitory processes following the excitatory drive from a single afferent nerve are factors in the sudden ending of the preganglionic reflex discharge (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of 'reversal' in somatic nerve experiments has been ascribed to greater temporal summation of impulses at higher frequency or to the presence in these nerves of fibres of different qualities (see Gordon, 1943). The reversals seen on changing the frequencies of stimulation of the carotid sinus and aortic nerves seem to result from the different frequency/response characteristics of the depressor and pressor mechanisms associated with these nerves.…”
mentioning
confidence: 99%